Smart contracts: fatores de decisão para adoção em empresas - Lopes, Alan Moreira (2020)
Theoretical research highlighted smart contracts as one of the applications for Blockchain technology capable of transforming business models and offering different benefits for companies that adopt this technological innovation. Considering that the blockchain is treated by theory as a technology deeply related to trust, the following benefits of the adoption of smart contracts were identified in the systematic review of the literature carried out through the Parsifal digital platform: security, agility resulting from automatic execution, availability, immutability, cost reduction compared to traditional contracts and automation. In view of these benefits, the researched theory indicated as factors considered for the adoption of smart contracts the legal validity, the increase of the efficiency of the processes, the reduction of operational costs, the decentralization, the automation and the security. This research sought to confirm the decision factors for the adoption of smart contracts pointed out by the theory. For this purpose, a systematic review of the literature was first carried out to survey the definition of smart contracts, their characteristics, which criteria should be considered for the adoption of this technology and which are the benefits arising from the adoption in companies. In this sense, the general objective established for this work was to understand the process of adopting smart contracts in companies. In order to make this general objective feasible, the following specific objectives were listed: identify if companies know smart contracts and what they are for, identify and analyze the factors that must be taken into account in the decision to adopt smart contracts and identify and analyze facilitating factors and barriers the adoption of smart contracts in companies. Taking into account the objective of understanding the mentioned phenomena, this dissertation is based on qualitative, exploratory and descriptive methodology. Data collection was carried out through semi-structured interviews with businessmen and technology professionals. In line with the proposed problem, the data collected were analyzed through content analysis based on the three phases indicated by Bardin. The data analysis confirmed in the interviewees’ statements the characteristics that define a smart contract, as well as the benefits and adoption factors raised in the theory. In addition, obstacles to adoption as political, cultural, interests of the minority that takes advantage of the great bureaucratization for monetary collection as the notaries, for example, emerged from the countryside. The practice of smart contracts in Brazil remains incipient, with legal challenges to be overcome and with prospects for applications in companies in the face of the pandemic scenario caused by COVID-19. This is a topic that deserves further research after the mentioned pandemic issue to improve the studies presented here.